PELATIHAN, PENDAMPINGAN MANAJEMEN, DAN DIGITALISASI DESA WISATA BRUMBUN KABUPATEN MADIUN MELALUI PENERAPAN APLIKASI E-COMMERCE - Iqbal Ramadhani Mukhlis (P3M Politeknik Negeri Malang, 2026)
Traditional promotion (word of mouth) and booking management (via WhatsApp) are major challenges for MSMEs and Pokdarwis in Brumbun Tourism Village. This community service activity aims to bridge this digital problem by designing and implementing appropriate technological solutions. The method used was the participatory development of the WooCommerce-based e-commerce application